Hubungan Sikap Ibu Tentang Pemberian Makanan Bayi Dan Anak (PMBA) Dengan Status Gizi Bayi Bawah Dua Tahun (Baduta) - Fatimah Sari; Evy Ernawati (Journal of Health (JoH), 2018)
Background: The growth and development in infants is very rapidly. The growth and development can be realized optimally when on the gold period, babies obtain the appropriate nutritional intake of Breast Milk is recommended as one of the exclusive source of nutrition in the first 6 months. Nutrition deficiency is suspected due to a lack of understanding of parents or proper nutritious food to the influence of advertising. They want to break the cycle of malnutrition that causes children short. Objective: This research aims to know the relationship of attitude about the feeding of infants and children (PMBA) with the nutritional status of infants under two years (BADUTA). Method: This type of research is descriptive analytic with cross-sectional approach. Research subjects who had a Mother Baduta in the village of Pandes Wedi Klaten Regency in Central Java. The way of determining the sample by the total sampling techniques. Instrument research using questionnaires conducted test validity and reabilitas. Analysis of data for the purpose of hypothesis testing using statistical tests Spearman Rho. Results: the attitude of Mothers in feeding on baduta with the results of positive mothers attitude that is as much as 100%. Baduta good nutritional status i.e. as many as 20 people (66.67%), nutritional Status of less baduta that is as much as 10 (33.33%). The results obtained bivariat relationship attitude mother with nutritional Status Baduta the value of p = 0,062 because > 0.05 p (p = 0,062 > 0.05) then it can be stated there was no relationship between maternal attitudes towards nutritional status of infants under two years of age. Conclusion: there is no relationship with the mother's nutritional status attitude baduta with a value of p = 0,062